Application of SDMA with scheduling for MIMO MC-CDMA - Monteiro, V. (2012)
Incoming Beyond 3G systems provides high data rates by using several techniques including Beamforming. Convenient DRA design is required to optimize the capabilities offered by smart antennas. This paper is to presents a DRA algorithm based on the HSDPA of UMTS, including scheduling that exploit SDMA technique that was implemented in the ambit of the IST 4MORE project. Results shown cell throughput gain of SDMA compared to sectorized cells about 76%, and that SDMA gain will increase with user diversity within the cell.